The constancy of the speed of light - Szymanski, Maciej B. (Physics essays, 2018)
The speed of light is normally assumed to be a fundamental constant of nature. In this essay, I propose that the speed of light is not a fundamental constant, but, rather, it is a consequence of the execution of fundamental laws of nature: primarily, the second law of thermodynamics and a law of gravitation. The implication is that the speed of light has to be constant and independent of the speed of the emitting source only when the light is subject to gravitation. This also means that the special theory of relativity is implicitly based on the existence of gravitational potential. The related implication is that the universe can be infinite in time as massless energy (photons) can accumulate and stars can form out of thermal radiation in the regions of the universe where no gravitational potential exists.